Attitude and Motivation of University Students in Learning English - Zulida, Abdul Kadir; Rosmahalil Azrol, Abdullah; Sarala Thulasi, Palpanadan; Siti Sara, Zainal Abidin; Siti Salmiah, Muhammad; Abdullah Adnan, Mohamed (UTHM, 2021)
The aim of this study is to examine the students’ motivation and attitude towards learning English as a second language from four Malaysian higher institutions. A random sampling of 471 respondents participated in this study. Using 28 items of an instrument, adapted from Gardner’s Attitude/Motivation Test Battery (AMTB), an online questionnaire was distributed to get the data. Students’ motivational level was found to be high with (M=6.37, SD=0.77, M=6.10, SD=0.82). Additionally, the respondents were having positive attitudes in learning English (M=4.07, SD=0.48). With the findings, it is hoped that this can be a guidance for instructors to design a suitable lesson and approach to be used in the language classrooms.